2010
DOI: 10.1179/174328910x12777566997739
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of UV irradiation cross-linked LDPE/EVA blends

Abstract: Ultraviolet induced cross-linking of low density polyethylene/ethylene vinyl acetate melt mixed blends were explored in presence of trimethylolpropane trimethacrylate (TMPTMA) and benzophenone (BP) as cross-linking agent and photoinitiator respectively. On the basis of gel content, it was found that 1 wt-%TMPTMA, 1 wt-%BP and irradiation time of 100 s represent the optimum parameters for photocross-linking of this system. Infrared spectroscopy was also used to follow the cross-linking reactions. Differential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…When crystalline polymers are irradiated by high-energy electrons or γ -ray, radicals generated in the crystalline regions have much lower mobility and longer lifetimes than those in the amorphous region because macromolecular diffusion movement is strongly hindered, and therefore they migrate to slowly amorphous phase [27]. A similar circumstance occurs in the photo-crosslinking process, and there have already been some reports which have confirmed it [20, 28]. Based on these facts, if more crystalline phase can be transferred to the amorphous phase, the efficiency of photo-crosslinking should be improved largely, so some films were photo-crosslinked at 55°C (around its T m ) to be compared with those at 25°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When crystalline polymers are irradiated by high-energy electrons or γ -ray, radicals generated in the crystalline regions have much lower mobility and longer lifetimes than those in the amorphous region because macromolecular diffusion movement is strongly hindered, and therefore they migrate to slowly amorphous phase [27]. A similar circumstance occurs in the photo-crosslinking process, and there have already been some reports which have confirmed it [20, 28]. Based on these facts, if more crystalline phase can be transferred to the amorphous phase, the efficiency of photo-crosslinking should be improved largely, so some films were photo-crosslinked at 55°C (around its T m ) to be compared with those at 25°C.…”
Section: Resultsmentioning
confidence: 99%
“…It is inferred that when the film is irradiated by UV light, BPs in PCL films can generate free radicals as analysed previously, which would then react and combine to form crosslinking networks in the films, and these networks could further provide the reinforcement effect to the films in resisting the applied straining stress. Longer irradiation time makes more BPs involved in generating free radicals, which form more crosslinking networks [20,30], so tensile strength gets higher. However, since the difference in gel fraction between PCL films with different BP contents is slight, changes between their tensile strength are very small.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blends of EVA with polymers such as low density PE and ethylene a-olefins have been studied extensively. [6][7][8][9][10][11][12][13] Maity and Das studies showed that polyurethane is able to cross-link with EVA at high temperatures without any curatives. The studies showed the blend properties largely depend on blend ratio and also blending techniques; also infrared studies showed that heating results in interchain cross-linking between PU and EVA.…”
Section: Introductionmentioning
confidence: 99%